Nature as a Romantic Aspect in George Bowering's Poetry - Haraj Al-Husseini, Sahar Abdul Ameer (Opción, 2019)
This research aims to demonstrate that George Bowering (1945) uses nature as one of his major themes in his poems via qualitative research method based on case study research methodologies. As a result, the poet tries to show his view about outward nature as being concurrent and congruous stating his position in nature as well as his awareness of it. As a conclusion, Bowering opts to presents haunting pictures to keep himself one with nature and consequently keeping himself with Canada and through this close association between humans and nature a new spiritual insight is going to be reciprocally produced.